Long-term management practices successfully reduce bird-related electrical faults in a transmission grid increasingly used by white storks for nesting. (1st February 2023) - Moreira, Francisco; Martins, Ricardo C.; Aguilar, Francisco F.; Canhoto, António; Martins, Jorge; Moreira, José; Bernardino, Joana
Abstract: Bird nests on transmission lines can cause electrical faults which reduce service reliability. To address this problem, since the mid-90s, the Portuguese Transmission System Operator (TSO) has undertaken management actions to discourage white storks Ciconia ciconia from nesting in hazardous locations of the pylons. Here, we compiled and analyzed an 18-year series of data on electrical faults, TSO management actions to tackle these, and stork nests on transmission pylons in Portugal to: (a) determine the relative importance of bird-related faults over the total number of faults; (b) describe variations in bird-related faults across time (season of the year and time of the day); (c) describe spatial variations in bird-related faults and their association with the occurrence of white stork nests on pylons; and (d) analyze the trends, over the years, of the number of white stork nests on pylons, the TSO management actions and their effectiveness in reducing bird-related fault rates. Overall, birds accounted, on average, for 25.3% of the electrical faults in the transmission network, with the vast majority being attributed to white storks. The seasonal pattern of bird-related faults showed higher rates in April and in October–November. Faults occurred more often during the night period, when storks spend more time on the pylons. We found a positive spatial relationship between the electrical fault rate and the proportion of pylons with stork nests (and the correlated number of nests per 100 km of line). There was, however, considerable variation in the fault rates not explained by the stork nest variables, particularly during the non-breeding season. The TSO management actions (namely removal/translocation of nests in hazardous locations of the pylons, installation of anti-perching devices and provision of alternative nesting platforms) significantly reduced, as a whole, the annual number of bird-related faults between 2001 and 2018, despite the three-fold increase in the number of white stork nests on transmission pylons. A deeper understanding of how white storks use the transmission pylons outside the breeding season is needed, so that targeted management actions can be taken to reduce the remaining bird-related fault rates to residual levels. Highlights: Storks were responsible for 25% of the electrical faults in the transmission grid. Faults were more likely during night, and during specific periods of the year. Spatial variations in fault rates were partly explained by stork nest abundance. TSO management effectively reduced fault rates, despite an increase in nest numbers.